10 We remember: a critical care COVID-19 remembrance service. (14th March 2023) - Norris, Ross; McCarthy, Jacqueline; Gray, David; Sundaram, Radha
Abstract : Background: There is increasing recognition that palliative care when provided appropriately to critically ill patients with life limiting illness can not only offer physical, psychosocial and spiritual care to patients but also helps improve family and staff satisfaction. 1 Given this, a multi-disciplinary group within the critical care unit of the Royal Alexandra Hospital was established to improve the delivery of palliative care. A staff survey highlighted the desire from staff to improve bereavement support for both families and staff. In light of this, the decision was made to host a remembrance service in memory of patients who had passed away in the unit during Covid-19 pandemic. Methods: Funding was secured from the charity To Absent Friends. The critical care database, Ward Watcher, was utilised to collate the details of patients who had passed away in the unit from March 2020 until August 2021. The number of patients identified was 237. The families of each patient were invited. A non-denominational remembrance service consisting of readings, live music and acts of remembrance was held in November 2022. Data: 13 staff and 40 families attended. 69% of staff who attended completed a feedback survey. 89% reported that the service brought them benefit and 100% reported that they would want the service to be held again. Written feedback from families included: 'The Service on Saturday became our 'closure' time and helped me get a new perspective on the last two years' Conclusions: Although the feedback received was limited, the data suggests that a remembrance service can be of benefit to both families and staff, particularly in the context of a pandemic when visiting was curtailed. This collaborative project has also demonstrated the need for further cross specialty working in order to ensure the delivery of palliative care within a critical care unit. Reference: Ito K, George N, Wilson J, et al . Primary palliative care recommendations for critical care clinicians. J Intensive Care 2022;10 :20. https://doi.org/10.1186/s40560-022-00612-9